Pemanfaatan Limbah Tandan Kosong Kelapa Sawit (Elaies Guineensis Jacq.) Sebagai Briket Bioarang - Meyrin Hamzah; Erni Mohamad; Nita Suleman; Ishak Isa; Wiwin Rewini Kunusa; Arviani Arviani (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the process of making oil palm empty fruit bunch briquettes through variations in tapioca flour as an alternative material, through the stages of research which include briquette making, namely drying, carbonization and printing. Briquette characterization includes proximate tests, namely water content, ash content, calorific value and densit. From the results of the proximate test at a ratio of 91:9, it shows that the quality of oil palm empty fruit bunch biochar briquettes with a moisture content of 7.07%, ash content of 8.769%, calorific value of 5850.2 cal/g and density of 0.55 g/cm3. The utilization of oil palm empty fruit bunches not only reduces waste, but also provides a solution for sustainable energy needs.